Intensity of Statin Treatment in Korean Patients with Acute Myocardial Infarction and Very Low LDL Cholesterol - Sim, Doo Sun; Jeong, Myung Ho; Kim, Hyo Soo; Gwon, Hyeon Cheol; Seung, Ki Bae; Rha, Seung Woon; Chae, Shung Chull; Kim, Chong Jin; Cha, Kwang Soo; Park, Jong Seon; Yoon, Jung Han; Chae, Jei Keon; et al. (Journal of lipid and atherosclerosis, 2019)
Data on the intensity of statin therapy for patients with acute myocardial infarction (MI) and very low baseline low-density lipoprotein (LDL) cholesterol level are lacking. We sought to assess the impact of statin intensity in patients with acute MI and LDL cholesterol <70 mg/dL. A total of 1,086 patients with acute MI and baseline LDL cholesterol <70 mg/dL from the Korea Acute Myocardial Infarction Registry-National Institute of Health database were divided into less intensive statin (expected LDL reduction <40%, n=302) and more intensive statin (expected LDL reduction ≥40%, n=784) groups. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCEs), a composite of cardiac death, MI, revascularization occurring at least 30 days after admission, and stroke, at 12 months. After 1:2 propensity matching, differences were not observed between less intensive (n=302) and more intensive statin (n=604) groups in incidence of cardiac death (0.3% vs. 0.3%) and hemorrhagic stroke (0.3% vs. 0.5%, =0.727) at 12 months. Compared with the less intensive statin group, the more intensive statin group showed lower target-vessel revascularization (4.6% vs. 1.8%, =0.027) and MACCE (11.6% vs. 7.0%, =0.021). Major bleeding was not different between less intensive and more intensive statin groups (1.0% vs. 2.6%, =0.118). More intensive statin therapy was associated with significantly lower major adverse cardiovascular events in patients with acute MI and very low LDL cholesterol compared with less intensive statin therapy.